Pengembangan Multimedia Pembelajaran Berbasis Lash Animation With Swish Max Siswa Kelas XI SMA Negeri 8 Kota Jambi - Harbeng Masni; Zuhri Saputra Hutabarat (Jurnal Ilmiah Dikdaya, 2019)
There are several factors that influence learning, including teacher factors, student factors, facilities, tools and media, and the environment. Educators should pay attention to factors that influence learning. The task of the teacher in the learning process, in addition to conveying information, also diagnoses learning difficulties students select teaching materials, supervise learning activities, stimulate student learning activities, provide learning guidance using media, strategies, and methods. Teachers and students are required to master the science and information technology of communication continuously. Teachers need to keep abreast of the development of communication information and science so that they can deliver the latest learning material that is useful for the lives of students in the present and future. The thing that stands out in Swishmax is that the work can be exported into the SWF file format, which is the file format used by Macromedia Flash. Therefore, swishmax animations can be played on any personal computer that has a flash player installed. Swishmax animations can be inserted into web pages, or imported into macromedia flash documents or even in Microsoft Power Point documents. When compared to adobe flash, Swishmax is easier to learn and use for beginners, because the tools available are more user friendly. From the description above it can be concluded that Swishmax is not only multimedia software that is only capable of creating dynamic multimedia, but more than that, it is capable of displaying multimedia that is very interactive.